Застосування дистанційних аерокосмічних методів для узагальненої оцінки стану ґрунтів регіону - Гебрин, Л.В.; Сахацький, О.І. (Геоінформатика, 2015)
Проаналізовано стан ґрунтів Закарпатської області на основі картограми ступеня деградованості земель станом на 2014 р. Визначено основні чинники зниження родючості ґрунтів сільськогосподарських угідь. Узагальнено наукові підходи до визначення зв’язку між спектральними каналами космічних знімків і вмістом поживних речовин у ґрунті. В результаті експерименту отримано лінійні регресійні залежності з високим значенням коефіцієнта детермінації між спектральною енергетичною яскравістю кожного пікселя у спектральних каналах (червоний (R), зелений (G) та блакитний (B)) космічного знімка супутника Landsat 8 OLI за березень 2015 р. і фактичними показниками вмісту гумусу на окремих полях у межах моніторингових ділянок. Виокремлено ділянки без наявності рослинності для підвищення точності методики за результатами розрахунку вегетаційних індексів (NDVI < 0,12). На основі отриманих регресійних залежностей побудовано показники гумусу в кожному пікселі знімка поля за спектральними характеристиками яскравості у червоному каналі. Запропоновано узагальнену методику оцінки стану ґрунту шляхом застосування аерокосмічної інформації, яка необхідна для здійснення агротехнічних заходів щодо покращення родючості сільськогосподарських земель і прийняття раціональних управлінських рішень на регіональному рівні. Дан анализ состояния почв Закарпатской области на основании картограммы степени деградации земель на 2014 г. Определены основные факторы снижения плодородия почв сельскохозяйственных угодий. Обобщены научные подходы к определению связи между спектральными каналами космических снимков и содержанием питательных веществ в почве. В результате эксперимента получены линейные регрессионные зависимости с высоким значением коэффициента детерминации между спектральной энергетической яркостью каждого пикселя в спектральных каналах (красный (R), зеленый (G) и голубой (B)) космического снимка спутника Landsat 8 OLI за март 2015 г. и фактическими показателями содержания гумуса на отдельных полях в пределах мониторинговых участков (МД). Выделены участки без наличия растительности для повышения точности методики по результатам расчета вегетационных индексов (NDVI < 0,12). На основании полученных корреляционных зависимостей определены показатели гумуса для отдельных полей в каждом пикселе снимка по спектральным характеристикам в красном канале. Предложена общая методика оценки состояния почвы путем применения аэрокосмической информации, необходимой для осуществления агротехнических мер по улучшению плодородия сельскохозяйственных земель и принятия рациональных управленческих решений на региональном уровне. Purpose. The developed generalized methods of assessment of soil based on ground and space information could be an effective toolkit providing information and supporting management decisions for soil monitoring. Application of such techniques would result in proper use of agronomic measures for improving soil fertility, providing specific information about the state of soil of the areas. Design/methodology/approach. The experimental studies were conducted using software Erdas Imagine 2014 for radiometric calibration and atmospheric correction of the image, as well as for determining the spectral signatures and data of spectral channels to further define the correlation dependency and humus definition pixels in each image. With the assistance of the software ArcGis was created mapped schemes of investigated territory. Findings. This article reveals close correlation with a high determination coefficients between the spectral energy brightness of each pixel in the channels (red R = 0,732, R = 0,673 green and blue R = 0,702) of satellite images Landsat 8 OLI and the actual indicator of humus content (Hav = 2,12) within the monitored areas of the administrative units of Transcarpathian region. The average vegetation indices of the studied area were determined (NDVI < 0, 12), as well as the value of humus in each pixel of image spectral characteristics in the red channel. Thus example, for MD 19 Solomonove, with the indicator of actual humus content of 1,86 (as of 2013), a predictive indicator of humus was found in the range of 0,67 to 1,34, which suggests a significant reduction in soil fertility on the area as of 2015. Practical value/implications. The study confirmed that the soils of Ukraine and its separate regions (Transcarpathian), quickly degrade and lose their nutritional value, especially humus. This trend makes them unsuitable for further use for agriculture, indicating the decline of agro-industrial complex as a whole. Ground methods of monitoring the crops condition are certainly effective, but it is a time-consuming expensive process. The generalized method of soil assessment that based on aerospace research is an efficient and reliable mechanism of management decision making sustainable agriculture.